Genetic Polymorphisms in RNF138, ABCA1 and ESRRG-GPATCH2 Genes and their Role in Insulin Resistance Risk among Normal BMI Individuals in Indian Population: A Case-control Study - Sabitha Thummala; Sarah Fathima; Nithya Kruthi; Junaid Ahmed Khan Ghori; Katherine Saikia; Vivek Belde; Balamurali Andiyakkal Rajendran; Rahul Ranganathan (Journal of Clinical and Diagnostic Research)
Introduction: India, characterised as the “diabetes capital” of the world, faces a rapidly increasing diabetes crisis, with over 65 million cases diagnosed. Despite the growing prevalence, the genetic underpinnings of Insulin Resistance (IR) among Indians with a normal Body Mass Index (BMI) remains understudied. Aim: To fill the knowledge gap by investigating the association of specific gene variants (RNF138, ABCA1, and Oestrogen-Related Receptor γ (ESRRG)-GPATCH2) with IR risk in this demographic. Materials and Methods: This study was a case-control study conducted in Bengaluru, Karnataka, India on a total of 191 participants (90 men and 101 women). The study, including data collection and analysis, was completed over a period of six months. Participants were categorised into cases (Homeostasis Model Assessment Insulin Resistance (HOMA2-IR) >2) and controls (HOMA2-IR <2) based on HOMA2-IR values. Genotyping for rs4799327 (RNF138), rs2275543 (ABCA1), and rs1497828 (ESRRG-GPATCH2) was performed using the Illumina Infinium Global Screening Array (GSA). Statistical analyses, including Odds Ratios (ORs), 95% Confidence Intervals (CIs), and inheritance model analysis, were conducted to assess the association between genotypes and IR. Results: Significant associations were found between IR and genetic variants rs4799327 (OR=2.74, 95% CI: 1.28-5.88, p-value=0.006) in RNF138, rs1497828 (OR=2.90, 95% CI: 1.51-5.57, p-value=0.0011) in ESRRG-GPATCH2 (dominant inheritance model), and rs2275543 (OR=3.50, 95% CI: 1.17-10.42, p-value=0.011) in ABCA1 (additive model). The study highlights a notable susceptibility to IR linked to these genetic markers among individuals with a normal BMI in the Indian population. Conclusion: This study underscores the importance of genetic factors in the risk of developing IR among Indians with a normal BMI, suggesting a complex interplay of genetics beyond traditional risk factors. These findings necessitate further research into the functional significance of these associations and their potential implications for targeted interventions and preventive strategies in high-risk populations.